Закономірності мембранного розділення дисперсних систем з урахуванням структурно-механічних параметрів фільтрувальних елементів та осаду - Пащенко, Богдан Сергійович (My University, 2020)
Дисертаційна робота присвячена вирішенню актуальних проблем дослідження закономірностей процесу мембранного розділення рідких дисперсних систем з урахуванням структурно-механічних параметрів керамічних фільтрувальних елементів та ущільнення шару осаду, що виникає на їхній поверхні. Розроблено метод теоретичного дослідження процесу мембранного фільтрування з урахуванням структурно-механічних параметрів фільтрувальних керамічних мембран та шару осаду, що виникає на її поверхні. Розроблено математичну модель ультрафільтрації з використанням керамічних фільтрувальних елементів, що ґрунтується на представленні фільтрувального елементу у вигляді пористого вологонасиченого каркасу разом із шаром осаду, який описується із використанням моделі континуально-дискретного дисперсного матеріалу. Досліджено вплив деформування керамічного мембранного елемента на кінетику ультрафільтрації рідких дисперсних систем, зміну пористості, проникності та критичного зниження продуктивності обладнання, механізм блокування прохідного перетину пори за рахунок деформування шару осаду. Виявлено, що внаслідок дії експлуатаційного навантаження основним фактором при зниженні продуктивності обладнання є ущільнення шару осаду. Одержані числові значення зміни пористості, коефіцієнтів проникності мембрани та шару осаду, а також час перекриття пор мембрани часточками осаду. Порівняння результатів розрахунків із даними фізичного експерименту свідчать про високу точність розробленого методу. Отримані результати досліджень впроваджені у виробництво та в навчальний процес Національного університету харчових технологій. The dissertation is devoted to the solution of urgent problems of investigation the regularities of the process of membrane separation of disperse systems, taking into account the structural and mechanical parameters of ceramic filter elements and the compaction of the sediment layer that occurs on their surface. Based on the analysis of the scientific literature and our own experimental studies it was found, that none of the theoretical models takes into account the deformation of ceramic filter elements during the ultrafiltration process which, together with the formation of a sedimentary layer, affects the characteristics of the membrane itself and the process parameters. The experimentally obtained numerical values and graphical dependences of the decrease in ultrafiltration productivity and the flow rate of the washing solution during the washing of the ceramic element on the duration of the process. This effect is caused by the change of the permeability coefficient of the membrane and the sediment layer on its surface. Investigation of the wear resistance of a ceramic element of an «Inopor» filter based on α-Al2O3 is carried out. The wear rate was determined by the weight loss of the specimen by the weight method. Analysis of the results showed that the nature of wear consists in the gradual accumulation of deformation energy and it’s abrupt on the surface of the membrane element release with the destruction of material. This is explained by the high content of α-Al2O3. A method has been developed for theoretical research of the process of membrane separation of liquid dispersion systems. A mathematical model of ultrafiltration with using ceramic filter elements has been developed, taking into account into account the structural and mechanical parameters of the membrane element and the sediment layer, patterns of change of their permeability coefficient. The design scheme of the ultrafiltration process based on the representation of the filter element in the form of porous moisture-proof framework containing a liquid dispersion system is developed. Such a continuum approach makes it possible to take into account the time variation of the sediment permeability coefficient under the action of operational load. The mechanism of overlapping the passage section of the pore due to the elastic-plastic deformation of the sediment layer is investigated. For this, on the basis of Slichter's theory, model of deformable porous continuous-discrete dispersed material is developed, that effectively reflects the nature of the porous structure change of the filtering medium. The developed algorithms are used as the basis of the created digital model PLAST-GiD, which consists of two subsystems: 1) PLAST-POR-M, which is designed to conduct computational experiments to study filtration processes, taking into account the stress-strain state of ceramic membrane elements; 2)PLAST-POR-M + GiD, is designed to conduct computational experiments to determine the quantitative parameters of irreversible deformation of the sediment layer and determine its permeability coefficient. The adequacy of the developed mathematical model was evaluated by comparing the obtained numerical values of specific productivity of the ultrafiltration process, the time to complete blocking of the passage of the liquid dispersion system through the pores and the permeability coefficient of filter element and sediment layer. The obtained numerical ratios of the values of simulation and physical modelling have a difference of 9%.
Keywords: мембранне розділення; рідкі дисперсні системи; деформація фільтрувальних елементів; ультрафільтрація; харчова промисловість; переробні виробництва; processing industries; membrane separation; liquid dispersion systems; deformation of filter elements; ultrafiltration; food industry; кафедра машин і апаратів харчових та фармацевтичних виробництв